ADOLESCENCE PERIOD AND PSYCHOLOGICAL FACTORS OF WORKING WITH TEENAGERS - Darvishxojayev Xasan Abdulhakimovich (American Journals Publishing, 2024)
Unique details of the adolescence period and psychological effects of working with adults having stressed are covered in this article. Useful suggestions are given to work with teenagers having depression.
Keywords: Stages of personal development, adolescence, transition period in a child, period of myself and depression.